Innovative Expansion of a University and Art Museum Partnership - Linda S. Larrivee; Joanne Gallagher Worthley; Susanna E. Meyer (The University of Alabama, 2022)
Many universities have partnerships with community organizations. However, the focus of traditional partnerships can be limited in scope. A partnership between a university and an art museum that traditionally focused on art and humanity classes was expanded and enhanced when faculty from two different departments not usually involved with the museum created novel projects. The projects were not paternalistic/theory-testing partnerships. Rather, one had characteristics of a professional/expertise partnership and the other was an empowerment/capacity-building partnership. These projects were designed to integrate foundational learning for students into solutions to real-life problems meaningful to students, the art museum, and the community in which the university and art museum were located. Universities may be well served to examine their current partnerships for innovative ways to benefit both institutions.